COST EFFECT OF BACKWARD GROWTH ON SUPPLY CHAIN IN THE INDUSTRIAL CATERING - Kudret GÜL; Melike GÜL (Dokuz Eylül Üniversitesi Sosyal Bilimler Enstitüsü Dergisi, 2017)
Abstract: In order to get competition advantage, reducing cost even a point is more essential in the industrial catering. The study focused on cost benefits of the backward growth among industrial catering firms in the supply chain. Thus, a survey was conducted on 7 backwards growth firms and 20 traditional working firms in the supply chain. Research results indicate that backwards growth decision of firms resulted positively with increase in stability of supply, competitiveness, firm’s market share, financial risk, firm’s profit and innovation, and negatively in coordination problems. In addition, backwards growth resulted with decrease in supply and inventory cost among vertical mergered firms in the supply chain. Competition in the industry, caterer and supplier relations, capacity utilization, advantages and disadvantages of backgrowth has been also investigated. Öz: Endüstriyel yiyecek işletmeciliğinde rekabet avantajı elde edebilmek için maliyetleri bir birim dahi azaltmak oldukça önemlidir. Çalışma, endüstriyel yiyecek işletmeleri arasında geriye doğru büyümenin maliyet kazanımlarına odaklanmaktadır. Bu doğrultuda tedarik zincirinde geleneksel olarak çalışan 20 firma ile geriye doğru büyüyen 7 firmaya yönelik bir araştırma yürütülmüştür. Araştırma bulguları firmaların geriye doğru büyüme kararının tedarikte istikrarı, rekabeti, pazar payını, finansal riski, firma karını ve yenilikçiliği olumlu yönde, koordinasyon sorunlarını ise olumsuz yönde etkilediğini göstermektedir. Araştırma bulguları geriye doğru büyümenin dikey olarak büyüyen firmalar arasında tedarik ve stok maliyetlerinde de azalma ile sonuçlandığını göstermektedir. Ayrıca çalışmada sektördeki rekabet, tedarikçi ve alıcı ilişkileri, kapasite kullanımı, geriye doğru büyümenin üstünlükleri ve sakıncaları da araştırılmıştır.